Analisis Penerapan Sistem dan Prosedur Akuntansi Dalam Pengelolaan Dana Desa (Studi Kasus Desa Grujugan, Kec. Larangan Kabupaten Pamekasan) - Rika Syahadatina; Yeyen Kurnia (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
This study aims to analyze the application of accounting systems and procedures in the management of Village Funds. The research was conducted in Grujugan Village, Larangan District, Pamekasan Regency. In order for village financial management to be accounted for, it must use a good and computerized village accounting system and in accordance with Minister of Home Affairs Regulation No. 113 of 2014 concerning village financial management. This research is a descriptive study using a qualitative approach. Sources of data used are primary data and secondary data. Data collection techniques in the form of interviews and documentation. The results of data collection were analyzed by data reduction, data presentation and conclusion drawing and verification. The results of this study indicate that the village fund financial accounting system in Grujugan Village has used the village financial system (Siskeudes) where the application is a complete application and can facilitate recording and reporting the Siskeudes application has been used in Grujugan Village since 2018 until now. The Siskeudes application is already equipped with a General Cash Book, a Tax Assistant Cash Book, and a Bank Book. Suggestions in this study need to increase the capacity of the village apparatus so that each component of the existing village apparatus can better understand and understand the duties and responsibilities of each.